Inside back cover: Biomarker discovery in mass spectrometry‐based urinary proteomics. Issue 4 (April 2016) - Thomas, Samuel; Hao, Ling; Ricke, William A.; Li, Lingjun
Abstract : DOI:10.1002/prca.201500102 Urine is among the most valuable sample materials for studies of human diseases. These urine solutes are shown with increasing approximate diameter from metabolite at 1 nm to protein at 5 nm to a group of exosomes at 100 nm each to a cell at 10 000 nm. This article highlights promising technologies and strategies in the mass spectrometry‐based urine proteomics and its application to disease biomarker discovery. Further details can be found in the article by Samuel Thomas et al. on page 358.